Reviewing and identifying the green criteria in relation to the building cost: project management - Naamandadin, Nurul Akmam; Sapian, Abdul Razak; Mustafa, Wan Azani; Awang, Arita Hanim; Abdul Razak, Rajabi; Abdul Rahman, Syakir Amir (Penerbit UTM Press, 2019)
To determine the similarities and differences categories of the assessments between the Malaysian green assessment tool for residential building with other countries, six (60 green assessments from six (6)different countries had been chosen; the United State (US) to represent the American region, the United Kingdom (UK)to represent Europe, Japan to represent Asia and Australia. Singapore was chosen as it is very close tot he location of the case study, Malaysia. Each of the countries represents different climate condition except for Singapore and Malaysia which experience the same climate. This paper will show a comparison of each selected green assessment tool under Management/Project Management criterion. The objective is to find out the potential benchmarks which can be applied in developing a cost modal prediction tool for the Malaysian green home.